2021
DOI: 10.1088/1755-1315/905/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The use of N HNO3 to determine copper and zinc levels in heavy-metal polluted tropical soils

Abstract: This study compared N HNO3 to other methods to determine plant available heavy metals in heavy-metal polluted soils. Soil samples were obtained from an experimental field treated with industrial waste after 22 years of the amendment and employed to conduct the comparative and correlation study. Soil samples were analyzed for Cu using various methods, planted in a glass house with several plants, and analyzed for soil and plant Cu and Zn. The relative strength of the chemical extractants followed the order of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The HNO 3 (nonexchangeable) extraction was also the method that best correlated with the absorption of Al, As, Cr, and Zn by plants ( r = 0.64, 0.70, 0.45, 0.71, respectively, p < 0.05). The PHE extracted from soils with dilute HNO 3 is considered geochemically active (Groenenberg et al, 2017; Melo et al, 2016) and is close to plant availability (Andrade et al, 2009; Salam et al, 2021). On the other hand, the correlation between PHE plant uptake and PHE pseudo‐total contents in DIW was not significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HNO 3 (nonexchangeable) extraction was also the method that best correlated with the absorption of Al, As, Cr, and Zn by plants ( r = 0.64, 0.70, 0.45, 0.71, respectively, p < 0.05). The PHE extracted from soils with dilute HNO 3 is considered geochemically active (Groenenberg et al, 2017; Melo et al, 2016) and is close to plant availability (Andrade et al, 2009; Salam et al, 2021). On the other hand, the correlation between PHE plant uptake and PHE pseudo‐total contents in DIW was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the following extraction methods were used for outer and inner sphere adsorptions: (i) exchangeable fraction with 0.5 M Ca (NO 3 ) 2 and (ii) nonexchangeable fraction with 1 M HNO 3 in a closed system. Potentially harmful elements extracted with dilute HNO 3 are also considered bioavailable and reactive fractions (Groenenberg et al, 2017;Salam et al, 2021). Andrade et al (2009) used different PHE extraction methods (DTPA-TEA pH 7.3; 0.5 M Ca(NO 3 ) 2 ; HNO 3 0.5, 1.0, and 4.0 M, and aqua regia [concentrated HNO 3 /HCl-3:1]) and concluded that nitric acid extractions should be preferred to establish the phytoavailability of Pb and Zn in contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…chemical extractant development, greenhouse correlation study, and field calibration test [24]. The development of chemical extractants is the initial step to devise particular extractants that may extract the intended forms of available heavy metals in the soil system [24,25]. As previously reported [25], heavy metals in the soil system exist in two major forms: dissolved heavy metals that include all forms in the soil water comprising free cations, complexes and chelates and the structural heavy metals comprising the exchangeable forms of heavy metal bounded on the negative charges of clays and organic molecules with various binding energies and the more strongly structural heavy metals in the soil secondary and primary minerals [24].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of each heavy metal form needs different chemical extractants [25]. Research reported in [25] studied the soil Cu extraction of 6 different extractants and showed that N HNO3 and N HCl extracted more Cu than did buffered and unbuffered DTPA as well as the weaker extractants including M CaCl2 and N NH4OAc pH 7.00.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation